Chemotherapeutic Strategies with Valnemulin, Tilmicosin, and Tulathromycin to Control Mycoplasma hyopneumoniae Infection in Pigs - Giovani Marco Stingelin; Marina Lopes Mechler-Dreibi; Gabriel Yuri Storino; Karina Sonalio; Henrique Meiroz de Souza Almeida; Fernando Antônio Moreira Petri; Luís Guilherme de Oliveira (MDPI AG, 2022)
Mycoplasma hyopneumoniae is the primary agent of Swine Enzootic Pneumonia (SEP). Vaccines reduce the clinical manifestation of the disease but do not prevent infection. The present study aimed to evaluate the use of antimicrobial drugs to minimize the impact of M. hyopneumoniae. For this, 32 pregnant female pigs and their litters were selected and then followed from birth to slaughter. The study involved three experimental groups that received metaphylactic treatment with different protocols involving tilmicosin, valnemulin, tulathromycin, and a control group to compare the effect of treatments against M. hyopneumoniae infection throughout the phases. Performance data were recorded, and the piglets were evaluated for the occurrence of cough. Nasal swab and blood collection was conducted periodically to detect M. hyopneumoniae shedding and anti-M. hyopneumoniae IgG, respectively. At slaughter, the lungs of animals from all groups were evaluated, and samples were collected for histopathological examination and qPCR for M. hyopneumoniae detection. All protocols promoted a reduction in consolidation lung lesions when compared to the control group. Individuals treated with valnemulin showed increased performance results, lower mortality, and low bacterial load in the lung. The results are promising and may indicate an alternative in the strategic control of M. hyopneumoniae infection in pigs.